Work Family Conflict dan Physchological Well Being Pada Nakes Yang Melanjutkan Pendidikan - Fadila, Dela; Pratiwi, Marisya (Program Studi Psikologi Fakultas Kedokteran Universitas Sriwijaya, 2020)
This study aims to determine the relationship between work family conflict and psychological well being in medical female civil servants who continue their education. The hypothesis is that there is a relationship between work family conflict and psychological well being in medical female civil servants who continue their education. The sample was 115 female civil servants who continued their education. The study used was purposive sampling technique. The scale used is the scale of work family conflict from Greenhaus & Beutell (1985) and scale of psychological well being from Ryff (1989). Data analysis is using Pearson product moment. The results show there are a relationship between work family conflict and psychological well being in female civil servants who continued their education r = -0,811 and p = 0,000 (p <0.05). This shows that work family conflict has a negative and significant relationship with psychological well being.